1990
DOI: 10.1002/hup.470050109
|View full text |Cite
|
Sign up to set email alerts
|

The use of flumazenil in prevention of Diazepam dependence in the rat

Abstract: Rats were treated with diazepam (4 mg/kg per day) or its vehicle for 21 days. Twentyâ\u80\u90four hours after their last dose they were tested in the social interaction test of anxiety. Diazepam withdrawal significantly reduced the time spent in social interaction compared with controls, indicating an anxiogenic withdrawal response. The administration of a single dose of flumazenil (4 mg/kg) during chronic diazepam treatment, 7 or 14 days before testing, prevented the development of this withdrawal response. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…These, and other Þndings have subsequently been interpreted as evidence that chronic benzodiazepine administration results in an adaptation of the GABA / benzodiazepine receptor complex which administration of ßumazenil is able to reset (Nutt and Costello 1988;Sannerud et al 1989;Baldwin et al 1990). The present Þndings might suggest that simply the experience of withdrawal is the important factor in protecting against the anxiogenic e¤ects of subsequent withdrawals, and that the implication of ßumazenil in the phenomenon is incidental.…”
Section: Exptmentioning
confidence: 91%
“…These, and other Þndings have subsequently been interpreted as evidence that chronic benzodiazepine administration results in an adaptation of the GABA / benzodiazepine receptor complex which administration of ßumazenil is able to reset (Nutt and Costello 1988;Sannerud et al 1989;Baldwin et al 1990). The present Þndings might suggest that simply the experience of withdrawal is the important factor in protecting against the anxiogenic e¤ects of subsequent withdrawals, and that the implication of ßumazenil in the phenomenon is incidental.…”
Section: Exptmentioning
confidence: 91%
“…In contrast, other studies (Baldwin and File 1989;Baldwin et al 1990), including studies in non-human primates (Lamb and Griffiths 1985;Gallager et al 1986), have demonstrated that exposure to flumazenil can attenuate the subsequent effects of flumazenil. For example, in rhesus monkeys treated daily with either 1.5 or 6.0 mg/kg diazepam (IM.…”
Section: Discussionmentioning
confidence: 76%
“…It has been suggested that this adverse consequence of long-term benzodiazepine use has influenced the frequency with which this class of drugs is prescribed and administered; thus, strategies to prevent the development of dependence might increase the clinical utility of benzodiazepines (Rickels et al 1983). Several preclinical studies have suggested that occasional exposure to flumazenil might retard the development of dependence, as evidenced by the reduced effectiveness of flumazenil in precipitating withdrawal signs in benzodiazepine-treated subjects (Lamb and Griffiths 1985;Gallager et al 1986;Baldwin and File 1989;Baldwin et al 1990); however, the generality of this finding has yet to be established. On the one hand, the failure of the current study to replicate previous reports suggests that the particular conditions under which the effects of benzodiazepine antagonists are assessed critically determine whether these effects change over time; on the other hand, the ability to reliably determine quantitatively similar dose-effect curves for flumazenil in benzodiazepine-treated monkeys suggests that other behavioral procedures, that require the frequent administration of antagonists, might be useful for studying benzodiazepines and that changes in sensitivity to the behavioral effects of flumazenil could be further exploited to study benzodiazepine dependence and withdrawal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This effect can be reversed by a single injection of the benzodiazepine antagonist, flumazenil (Gonsalves and Gallager, 1985;Nutt and Costello, 1988). Repeated administration of flumazenil prevents benzodiazepine withdrawal signs in Rhesus monkeys (Gallager, Heninger and Heninger, 1986), and even a single dose can prevent diazepam dependence in the rat (Baldwin, Hitchcott and File, 1990). However, two studies using flumazenil suggest that tolerance and physical dependence may be distinct phenomena with the benzodiazepines (Lamb and Griffiths, 1985;Loscher and Rundfeldt, 1989).…”
Section: Introductionmentioning
confidence: 95%